أثر التسويق الداخلي في جودة الخدمة الفندقية - وريدة, ثابت; نزيهة, زابي; عبلة, حمادي (University of eloued جامعة الوادي, 2021)
"هدفت دراستنا إلى تسليط الضوء على تحديد أثر التسويق الداخلي على جودة الخدمة الفندقية ابتداءا من متغيريين رئيسيين التسويق الداخلي كمتغير مستقل والذي تم قياسه بالأبعاد التالية مدى اعتماد المؤسسة على التسويق الداخلي علاقة الموظفين فيما بينهم وكمتغير تابع جودة الخدمة الفندقية ولقد ارتكزت مشكلة الدراسة حول اثر التسويق الداخلي على جودة الخدمة الفندقية بالاعتماد على مجموعة من الفرضيات لحل هذه المشكلة. ومن أجل تحقيق أهداف الدراسة وفرضياتها قمنا باتباع المنهج الوصفي التحليلي لإختبار هاته الفرضيات و التي تم قياسها من خلال الإستبيان الذي قمنا بتصميمه موجه للموظفيين وتم توزيعه لدى مجموعة من المؤسسات الفندقية بولاية الوادي حيث اعتمدت الدراسة في جانبها التطبيقي على برنامج واختتمت الدراسة بمجموعة من التوصيات والاستنتاجات التي تم التوصل إليها من خلال الدراسة الميدانية حيث استنتجنا مدى ارتباط التسويق الداخلي بجودة الخدمة الفندقية ووجود مستو مرتفع لكلا الأخيرين حيث أن جودة الخدمة تتحقق بوجود تسويق داخلي و لتحسين المؤسسة الفندقية صورتها ورفع بمكانتها يجب أن تهتم بمواردها البشرية وتسعى لتلبية ظروف جيدة لموظفيها. الكلمات المفتاحية: التسويق الداخلي جودة الخدمة الفندقية"Our study aimed to shed light on determining the impact of internal marketing on the quality of hotel service, starting from two main variables, internal marketing as an independent variable, which was measured by the following dimensions: the extent to which the institution depends on internal marketing, the relationship of employees among them, and as a dependent variable on hotel service quality. The study problem was based on the impact of marketing Internal on the quality of hotel service based on a set of hypotheses to solve this problem. In order to achieve the objectives of the study and its hypotheses, we followed the descriptive analytical approach to test these hypotheses, which were measured through a questionnaire that we designed for employees and distributed to a group of hotel establishments in El-Wadi State. It was reached through the field study, where we concluded the extent to which internal marketing is related to the quality of hotel service and the presence of a high level for both of the latter, as the quality of service is achieved by the presence of internal marketing and for the hotel establishment to improve its image and raise its standing, it must take care of its human resources and seek to meet good conditions for its employees. Keywords: internal marketing...
مذكرة ماستر تسويق سياحي وفندقي
Keywords: التسويق، الداخلي ،جودة الخدمة الفندقية; Internal، Marketing Hotel ،Service Quality